Antimicrobial susceptibility, auxotype and plasmid content of Neisseria gonorrhoeae in northern Tanzania: emergence of high level plasmid mediated tetracycline resistance. Issue 1 (February 1995) - West, B; Changalucha, J; Grosskurth, H; Mayaud, P; Gabone, R M; Ka-Gina, G; Mabey, D
Abstract : OBJECTIVE--To study the antimicrobial susceptibility, plasmid content, auxotype and serogroup of strains of Neisseria gonorrhoeae isolated from an urban population of STD clinic attenders in Northern Tanzania. METHODS--The minimum inhibitory concentrations of nine common antimicrobial agents were measured by the agar dilution method against 130 strains of Neisseria gonorrhoeae isolated in a free government STD clinic in Mwanza town. The auxotype, plasmid content and serogroup of these strains were also determined by conventional techniques. RESULTS--65 strains (50%) were penicillinase producers (PPNG), and 34 (26%) exhibited chromosomally mediated resistance to penicillin. Seven (5%) were sensitive to tetracycline; 78 (60%) showed intermediate levels of resistance, and 45 (35%) had high level plasmid mediated resistance (TRNG), all of which carried a 25.2 MDa plasmid. 79 strains (61%) showed decreased sensitivity to trimethoprim-sulphamethoxazole, and five (4%) were resistant to this agent. All isolates were fully sensitive to spectinomycin, azithromycin, cefotaxime, cefuroxime, norfloxacin and ciprofloxacin. One hundred and one strains (78%) were of type W11/111, 22 type W1, and seven cross reacting strains. The W1 strains were significantly more likely to be carrying plasmid mediated resistance to both penicillin and tetracycline. Six different auxotypes were present, the major type requiring proline. Plasmid profiles showed the presence of both the 3.2 MDa and the 4.4 MDa beta-lactamase encoding plasmids. CONCLUSION--a high proportion of gonococcal isolates remain resistant to penicillin in this region, and most isolates are now also resistant to tetracycline, with the emergence of plasmic mediated tetracycline resistance. Trimethoprim-sulphonamide sensitivity is also decreasing. The population of strains is heterogeneous, and both African and Asian beta-lactamase encoding plasmids are present.